Coronavirus disease 2019 (COVID-19) personal protective equipment training: Using simulation-based training to prevent healthcare-associated infection - Madhuri B. Nagaraj; Krystle K. Campbell; Minji Kang; Ian A. Nazareno; Doramarie Arocha; Julie B. Trivedi; Daniel J. Scott (Cambridge University Press, 2022)
In this pre- and postintervention study, we demonstrate the feasibility and effectiveness of comprehensive simulation-based personal protective equipment (PPE) training amid the COVID-19 pandemic. With rapid-cycle, deliberate practice feedback, simulation-based training can improve the learners' sense of confidence and security while standardizing PPE protocols.